Truth-in-voting: election reform and Manhattan community - Romanova, Kate (My University, 2015)
This report is the result of a research on voting technological innovations and regulations, which are required by the Help America Vote Act of 2002. It looks into HAVA activities and implements in various states and particular in Riley County, Kansas. It analyzes the impact of DREs on voting activities and Manhattan community.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Romanova, K. (2006). Truth-in-voting: election reform and Manhattan community. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: United States. Help America Vote Act of 2002; Election law--Kansas; Voting-machines--Law and legislation--Kansas; Voting $$z Kansas $$z Riley County; Reports; Reports